Analisis pengaruh keberadaan Hutan Alas Pala sebagai ruang terbuka hijau terhadap aktivitas masyarakat Desa Sangeh - Anak Agung Ayu Oka Saraswati; Anak Agung Ngurah Aritama; I Dewa Gede Krisna Adrias Putra; Fanedya Agfyrla Oriondina; Dewa Rai Prema Satya Buana; Gede Bagus Paundra Maharathah; Anak Agung Ngurah Jaya Adnyana (Jurnal Arsitektur Lansekap, 2025)
Environment contributes a significant role to influence how the community functions. One of the key values of a great environment is a well qualified green space. As an area, green open spaces are important for advancing communities, including decreasing the negative impact of city development which is a crucial part of building civilization. In this article we are focusing on the most important open green space on Sangeh village, Alas Pala Forest, which managed by the community, Alas Pala Forest has total land dimensions of 13,91 hectare, thus this article focusing on a study about how the people of Sangeh is affected by it. The method used is data collection, observation, interview, and questionnaire. The result from this research proved that the existence of Alas Pala Forest as a green space indeed has impacts on community activities of Sangeh Village. This study researches in depth aspects, ranging from economical to social and cultural aspects on the activity of Sangeh community. These benefits include the increased of tourist numbers, the development of MSMEs, job creation, and strengthening social interaction and preserving local culture. Environmentally, Alas Pala Forest contributes to maintaining air quality, conserving flora and fauna, and maintaining ecosystem stability. Furthermore, it offers physical and psychological health benefits.